2015
DOI: 10.4137/sart.s23502
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Mind in Mind: Mentalizing and Executive Functioning in Substance-Abusing Infant Mothers: Effect on Dyadic Relationship and Infant Outcome

Abstract: Although it is well documented that maternal substance abuse has a negative effect on the mother–child interaction, less is known about the pathways through which the interaction is compromised. The main objective of this research proposal is to describe an ongoing research project that focuses on associations between maternal executive function and the quality of mother–infant interaction when the mother has a history of substance abuse. We will also investigate the effects of multiple variables, including ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…These two areas are functionally connected to prefrontal cortical regions during emotion regulation through the use of cognitive strategies, such as reappraisal ( 29 ). The same substrates are implicated in drug consumption pathways that impair executive function, a multidimensional construct that includes, besides emotion regulation, a suite of cognitive operations like mental flexibility, inhibition, planning, working memory, reflective functioning ( 30 ), verbal fluency ( 31 ), and language ( 22 , 32 ).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two areas are functionally connected to prefrontal cortical regions during emotion regulation through the use of cognitive strategies, such as reappraisal ( 29 ). The same substrates are implicated in drug consumption pathways that impair executive function, a multidimensional construct that includes, besides emotion regulation, a suite of cognitive operations like mental flexibility, inhibition, planning, working memory, reflective functioning ( 30 ), verbal fluency ( 31 ), and language ( 22 , 32 ).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In this context, the concept of sensitivity implies the capacity to detect and accurately understand the child's signals and to respond appropriately according to the child's needs. This skill requires reflective abilities, such as mentalization, which appears to be impaired in drug-abusing mothers with regard to meeting the baby's needs and their own parental competencies ( 31 ). Frequently, mothers with low mentalizing capabilities attributable to substance use misunderstand infant behaviors, interpreting them as rejecting, and hence construct a representation of their child as intrusive, detached, or hostile ( 31 , 42 ).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have investigated the relation between parental neuropsychological functioning and parenting in individuals with SUD [ 49 , 50 ]. For example, recent research by Håkansson and colleagues [ 50 ] investigated the associations between EF and parental reflective functioning in caregivers with SUD, which includes the caregiver's ability to recognize the child's expressions and behaviors as well as the caregiver's appreciation that the inner world of the child may be affected by the inner world and mental state of the parent.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The authors found significant associations between these two domains, suggesting that they may both be essential in sensitive caregiving. This may be because adequate functioning of these domains enhances accurate perception, interpretation, and responsiveness to infant cues [ 49 ]. To our knowledge, the current study is the first study to examine the associations between parental neuropsychological functioning and the quality of observed parent-child interactions in the context of parental SUD.…”
Section: Theoretical Backgroundmentioning
confidence: 99%